Consumption and rate of passage of digesta in buffalo calves (Bubalus bubalis) fed star grass (Cynodon nlemfuensis) and protein-energy supplementation - L?pez, Jos? Ra?l; El?as, Arabel; Delgado, Denia; Sarduy, Luc?a; Dom?nguez, Marbelis (Cuban Journal of Agricultural Science, 2014)
Four buffalo calves (Bubalus bubalis) of the Buffalypso breed of 10 months of age and 214 ? 5 kg live weight were used. Animals were rumen cannulated and fed poor quality star grass for determining the effect of protein-energy concentrate supplementation on consumption and rate of passage of the liquid and solid fractions through the rumen. Four treatments were assessed with different amounts of concentrate in the diet: 0, 3, 6 and 9 g/kg LW offered once daily (8:00 a.m.), according to a 4 x 4 Latin square experimental design. Nutrient consumption was measured by supply and rejection. The determination of the passage of the liquid fraction was made at 2, 4, 6, 8, 12, 16 and 24 h after supplying the Co-EDTA marker. For the solid fraction chromium impregnated forage was used, with direct feces collection from the rectum and until 144 h after marker dosage. Supplementation, up to 9 g/kg LW with concentrate, allowed the increase (P < 0.001) of total dry matter consumption (DMC) and there were no differences in DMC of forage (kg animal-1 day-1) between treatments. Total consumption of NDF was higher (P < 0.05) for the treatment with 6 g/kg LW regarding the control. The supplementation did not affect the passage indicators of the liquid and solid fractions through the rumen in buffalo calves. The rate of passage of the liquids was between 5.63 and 6.48 %h and rechangings between 1.35 and 1.55 times/d. The rate of passage of solids through the rumen ranged between 3.01 and 4.48 %/h. The rate of passage of solids by the rumen ranged between 3.01 and 4.48 %/h. Similar performance showed the passage of the solid fraction by the cecum-proximal colon with values between 5.88 and 7.16%/h. Supplementation with concentrates in buffalo calves consuming poor quality forage propitiated the increase of total nutrient consumption, without altering DMC of forage and the passage indicators. These results constitute elements that must be considered for developing nutritional strategies for this animal category. Key words: Buffalypso, buffalo calves, consumption, passage